Uji Ketahanan Beberapa Varietas Cabai (Capsicum sp.) Terhadap Penyakit Antraknosa (Colletotrichum sp.) yang Berasal Dari Desa Hiyung Kabupaten Tapin - Afridha Laila Adhni; Dewi Fitriyanti; Elly Liestiany (www.ulm.ac.id, 2022)
The purpose of this study was to test the resistance of four chili varieties (Capsicum sp.) to anthracnose (Colletotrichum sp.). The research was carried out at the Phytopathology Laboratory and in the Phytopathology Greenhouse Land, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. This study used 4 varieties, namely Taruna variety, Hiyung variety, CF-291 variety and Tanjung variety with 5 replications. The Tanjung variety has the longest incubation period of 10 days, while the CF-291 variety has the fastest incubation period of 7.5 days. The CF-291 variety showed a susceptible variety with a percentage of 41.3% while the Taruna, Hiyung and Tanjung varieties showed a moderate variety with a percentage of 34.1%, 23.1 and 32.7%, respectively.